Seeking Health Information and Social Support in the Diabetes Online Community - Hughes, Allyson; Heydarian, Nazanin; Gerardo, Diana; Solis, Isabela; Morera, Osvaldo (Frontiers in Clinical Diabetes and Healthcare, 2021)
Purpose: People with type 1 diabetes (T1D) search for health information online in the Diabetes Online Community (DOC), where individuals with diabetes, researchers and caregivers post and respond to health questions. The aims of this study were 1) to understand how people with T1D are seeking health information and engaging in health behaviors in the DOC, and 2) develop a measure of online health information seeking in adults with T1D. Research Method: Ninety-five adults with T1D completed qualitative prompts online. Results: Themes that emerged in this study included sense of community, and multiple types of social support that are necessary in disease management. Conclusions: This study used qualitative methods to develop a valid scale tailored for adults with T1D. Future research should seek to collect additional data to bolster validity and reliability.